Alterations of mitochondrial bioenergetics, dynamics, and morphology support the theory of oxidative damage involvement in autism spectrum disorder. Issue 5 (4th April 2020) - Pecorelli, Alessandra; Ferrara, Francesca; Messano, Nicolò; Cordone, Valeria; Schiavone, Maria Lucia; Cervellati, Franco; Woodby, Brittany; Cervellati, Carlo; Hayek, Joussef; Valacchi, Giuseppe
Abstract: Autism spectrum disorder (ASD) has been hypothesized to be a result of the interplay between genetic predisposition and increased vulnerability to early environmental insults. Mitochondrial dysfunctions appear also involved in ASD pathophysiology, but the mechanisms by which such alterations develop are not completely understood. Here, we analyzed ASD primary fibroblasts by measuring mitochondrial bioenergetics, ultrastructural and dynamic parameters to investigate the hypothesis that defects in these pathways could be interconnected phenomena responsible or consequence for the redox imbalance observed in ASD. High levels of 4‐hydroxynonenal protein adducts together with increased NADPH (nicotinamide adenine dinucleotide phosphateoxidase) activity and mitochondrial superoxide production coupled with a compromised antioxidant response guided by a defective Nuclear Factor Erythroid 2‐Related Factor 2 pathway confirmed an unbalanced redox homeostasis in ASD. Moreover, ASD fibroblasts showed overactive mitochondrial bioenergetics associated with atypical morphology and altered expression of mitochondrial electron transport chain complexes and dynamics‐regulating factors. We suggest that many of the changes observed in mitochondria could represent compensatory mechanisms by which ASD cells try to adapt to altered energy demand, possibly resulting from a chronic oxinflammatory status.